An Empirical Study of Coastal Tourism Development Strategy in Pasir Padi Beach of Pangkalpinang City Indonesia - Eddy, Khalimo Tabarani (FIA UB, 2016)
This paper examines how the local authorities strategies to develop coastal tourism using Integrated Coastal Zone Management as a sustainable tourism in Pangkalpinang City that can give benefits for social, economic, and environmental, and can overcome the constraining factors that authorities faced. The results show that for development is not running well in practice, in so far as strategic planning should be consistent among strategies, goals, orientation, and implementation. This is a challenge for local authorities to be able to coordinate with the private sector and local communities in developing sustainable tourism.